Question Number 10268 by j.masanja06@gmail.com last updated on 01/Feb/17

Answered by sandy_suhendra last updated on 01/Feb/17

(x−3)(x+5)(x−1)+6+42−6(x+5)+6(x−3)+7(x−1)=0  x^3 +x^2 −10x+8=0  (x−1)(x^2 +2x−8)=0  (x−1)(x−2)(x+4)=0  x=1 or x=2 or x=−4

Answered by arge last updated on 04/Feb/17

x−3    1        −1    −7     x+5    −1     −6        6     x−1    x−3     1        −1    −7     x+5     −1      (x−3)(x+5)(x−1)+(−7×6×−1)+(−6×1×−1)−{−1(x+5)(−6)+[−1(6)(x−3)+(x−1)(1)(−7)}=0  x^3 +x^2 −24x+22=0  (x−1)(x^2 +2x−22)=0    x=1